Physiological determinants of nitrogen dynamics in response to genotype by management interactions in US maize hybrids - Fernandez, Javier Antonio (Kansas State University, 2021)
In maize (Zea mays L.), the largest staple crop in the world, nitrogen (N) represents a major limiting factor for productivity. However, improving N use efficiency (NUE) is still one of the most critical research issues to achieve food security in a context affected by climate change. This dissertation is structured in six chapters (Chapter 1, Introduction, and Chapter 6, Conclusions) outlining the agronomic and physiological traits associated with a better N utilization in US maize hybrids across Genotype × Environment × Management (G × E × M) conditions, with emphasis on the implications of long-term genetic selection. Chapter 2 presents a comprehensive meta-analysis on a diverse dataset assembled from field studies from 1983 until 2018 to compare early- versus late-season N (applied after tenth-leaf) fertilization effects on yield and N recovery efficiency. Results provided evidence for the lack of a main effect of late N application on yields but suggest the existence of crop growth conditions prone to a greater reproductive N uptake where this practice might be suitable. Throughout multiple field trials, Chapter 3-5 advanced in our understanding of how long-term genetic improvement has modified N dynamics across G × M scenarios. Chapter 3 proposes a novel N by carbon (C) framework to analyze and define key morpho-physiological traits of breeding interest that allow modern maize plants to achieve higher productivity and NUE. Results show both an earlier stem N remobilization and a decline in grain N concentration are key drivers of N utilization efficiency in modern hybrids. Chapter 4 documents the underlying fluxes of post-flowering N allocation and translocation dynamics behind genetic improvement over time in field-grown corn. This research suggests that direct selection for yield has indirectly favored N allocation to leaves in modern genotypes resulting in an improved post-flowering C accumulation. Finally, Chapter 5 explores historical changes in the contribution of grain weight and its physiological characteristics to maize genetic progress. This research evidences a significant contribution of increments in grain weight in US maize but concludes the trade-off between grain number and weight poses a challenge for future yield progress.
Keywords: Crop physiology; Corn; Nitrogen; Carbohydrates; Yield; Genetic gain